Intelligent Distributed Computing X Proceedings of the 10th International Symposium on Intelligent Distributed Computing - IDC 2016, Paris, France, October 10-12 2016 - Badica, Costin; El Fallah Seghrouchni, Amal.; Beynier, Aurélie; Camacho, David; Herpson, Cédric; Hindriks, Koen.; Novais, Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents the combined peer-reviewed proceedings of the tenth International Symposium on Intelligent Distributed Computing (IDC'2016), which was held in Paris, France from October 10th to 12th, 2016. The 23 contributions address a range of topics related to theory and application of intelligent distributed computing, including: Intelligent Distributed Agent-Based Systems, Ambient Intelligence and Social Networks, Computational Sustainability, Intelligent Distributed Knowledge Representation and Processing, Smart Networks, Networked Intelligence and Intelligent Distributed Applications, amongst others.
Adaptive Scaling Up/Down for Elastic Clouds.-A Dynamic Model to enhance the Distributed Discovery of SWs in P2P Overlay Networks -- Simulation of Dynamic Systems Using BDI Agents: Initial Steps.-A Multi-Agent Middleware for the Deployment of Distributed Applications in Smart Environments -- A Guidance of Ambient Agents Adapted to Opportunistic Situations Extended Context Patterns - A Visual Language for Context-Aware Applications.-MDE4IoT: Supporting the Internet of Things with Model-Driven Engineering.-Detection of traﬃc anomalies in multi-service networks based on a fuzzy logical inference.-Reconﬁguration of RBAC schemes by genetic algorithms.-String-based Malware Detection for Android Environments -- Optimal Conﬁguration Model of a Fleet of Unmanned Vehicles for Interoperable Missions .-Spatial Tuples: Augmenting Physical Reality with Tuple Spaces -- Exploring unknown environments with multi-modal locomotion swarm -- Group Trust: Finding Trust-based Group Structures in Social Communities -- Non-intrusive Monitoring of Attentional Behavior in Teams -- A Speculative Computation Approach for Conﬂict Styles Assessment with Incomplete Information -- Forming Classes in an e-Learning Social Network Scenario.-Scheduling Optimization in Grid with VO Stakeholders' Preferences -- On the Application of Bio-inspired Heuristics for Network Routing with Multiple QoS Constraints.-Dealing with the Best Attachment Problem via Heuristics.-Towards Collaborative Sensing using Dynamic Intelligent Virtual Sensors .-Intelligent Data Metrics for Urban Driving with Data Fusion and Distributed Machine Learning.-A Probabilistic Sample Matchmaking Strategy for Imbalanced Data Streams with Concept.-Author Index. .
Keywords: Computational intelligence; Artificial intelligence; Data mining; Computational Intelligence; Artificial Intelligence; Data Mining and Knowledge Discovery